Treasury Single Account and Performance of the Public Sector in Nigeria - Nkanbia-Davies; Lilian Okorite; Okafor; Chinyere; Penu; Samuel; Lucky (International Journal on Economics, Finance and Sustainable Development, 2022)
This study examined the relationship between Treasury Single Account and the performance of public sector in Nigeria. Quarterly secondary data were sourced from Central Bank of Nigeria’s Statistical Bulletin over the period 2010Q1 to 2020Q2. The paired-sample t-test as well as the Least Squares regression estimation techniques were employed to analyze whether significant differences existed in government revenue, expenditure, debt and GDP before and after the implementation of TSA as well as to ascertain the effect of TSA on the economy. Findings revealed that TSA has an insignificant negative influence on GDP and concluded that TSA implementation has not contributed positively to GDP in Nigeria. The study recommended that government should reappraise existing fiscal policy framework in order to enhance macroeconomic performance. Further, the legal framework for TSA should be reinforced to improve disbursement efficiency so as to ensure that it is not used as a tool in achieving political dominance.